TOKEN BASED APPROACH FOR RESOURCE MANAGEMENT IN IOT EDGE NETWORKS - Aubakirov, Yernur; Tursyn, Yersultan; Maratov, Yerassyl; Sakenuly, Meiirkhan; Kadirov, Nukhan (Nazarbayev University School of Engineering and Digital Sciences, 2025)
The growth of the Internet of Things has created challenges in managing network resources and preventing mali- cious users from exploiting the system. Traditional networking approaches lack scalability and the flexibility to adapt to dy- namic resource demands. This project presents an approach to managing IoT edge networks using SDN (Floodlight), simulated blockchain token systems (Ganache), and Dockerized IoT nodes. We successfully implemented a system that filters abnormal requests, incentivizes computational fairness, and visualizes token balance over time. Results show effective request management and traceable resource consumption using blockchain logic.
Keywords: IoT; Resource Management; Token-Based Sys- tems; Software-Defined Networking (SDN); Blockchain; Edge Computing; Network Security; Smart Contracts; Malicious User Prevention; type of access: open access